SEARCH FOR R-PARITY VIOLATING DECAYS OF SUPERSYMMETRIC PARTICLES AT LEP - PÁSZTOR, GABRIELLA (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2001)
Searches for pair-produced charginos neutralinos and scalar fermions decaying via R-parity violating λ, λ′ and λ′′ couplings with the OPAL detector at LEP are presented at $\sqrt{s} = 189~{\rm GeV}$ . Partial updates using data up to the highest energies of LEP, $\sqrt{s} = 209~{\rm GeV}$ , are also given.